Analisis Kegagalan Material Patahnya Coil Spring pada Track Adjuster Excavator PC 78 - Leo Adi Saputra; Santoso, Nugroho; Setyana, Lilik Dwi; Basuki, Budi (Jurnal Teknologi dan Rekayasa Alat Berat, 2025)
One of the critical components of an excavator's undercarriage is the coil spring, which frequently breaks due to extreme working conditions, lack of routine maintenance, and material defects. This coil spring failure often occurs in the PC 78 excavator unit. The resolution of this issue requires an undetermined period of time. This problem can lead to decreased and suboptimal excavator productivity. The objective of this study is to identify the causes of coil spring fractures, evaluate its mechanical strength, and determine the type of material used. The methods applied include chemical composition analysis, microstructure examination, hardness testing, and impact testing. Visual observations indicate that the coil spring failure is caused by material fatigue, crack initiation, propagation, and final fracture characterized by beach marks and striations. Chemical composition analysis reveals the dominance of iron (Fe), carbon (C), chromium (Cr), and manganese (Mn), classifying the material as AISI 51xx steel. Microstructural examination shows a dominance of bainite, which contributes to the material's hardness. Vickers hardness testing indicates high hardness values consistent with the observed microstructure. Impact testing results suggest that the fractured specimen exhibits ductile behavior.